Effects of gamma irradiation on the fatty acids profile of Lactarius deliciosus wild mushroom - Fernandes, Ângela (2012)
The short shelf-life of mushrooms (1-3 days at ambient temperature) is an impediment to the distribution and marketing of the fresh product. Despite of the immense popularity of this food all over the world data regarding alternative technologies to increase mushrooms shelf-life are scarce. Treatment by irradiation emerges as a possible conservation technique that has been tested successfully in several food products and is regulated in the European Union by the Directive 1999/2/EC. Herein, the influence of gamma irradiation dose (0.5 and 1 kGy) over the fatty acids profile of Lactarius deliciosus L. wild mushroom, collected in the Northeast of Portugal (November 2011), was evaluated by gas-chromatography coupled to flame ionization detection (GC-FID). The analyses were performed after 0 (control), 4 and 8 days of storage at 4 oC. The control and the irradiated samples revealed an identical profile, with C18:0 (stearic acid), C18:2n6c (linoleic acid), C18:1n9c (oleic acid) and C16:0 (palmitic acid) as the main fatty acids. These results are in agreement to the reported by our research group in a previous study with nutritional characterization of this species [1]. Nevertheless, some differences were found in the percentage of some fatty acids in the different samples. For instance, control sample (non-irradiated) after 8 days of storage, showed a lower C18n1n9 percentage (decreased from 8 to 4.4%) contributing to a decrase in MUFA levels. Otherwise, in the sample irradiated with 0.5 kGy the percentage of the mentioned fatty acid did not changed until day 8. Overall, irradiation could be an alternative to ensure the quality and extend the life of mushrooms, protecting their fatty acids composition.